Maternal and fetal outcomes in multiparous women with Cystic Fibrosis - Cohen-Cymberknoh, Malena; Ariel Dabby, Maya; Gindi Reiss, Bar; Melo Tanner, Joel; Pérez, Gema; Lechtzin, Noah; Polverino, Eva; Perez Miranda, Javier; Gramegna, Andrea; Aliberti, Stefano; Levine, Hagit; Mussaffi, Huda; et al. (Respiratory medicine, 2024)
BACKGROUND: Quality of life and survival in Cystic Fibrosis (CF) have improved dramatically, making family planning a feasible option. Maternal and perinatal outcomes in women with CF (wwCF) are similar to those seen in the general population. However, the effect of undergoing multiple pregnancies is unknown. METHODS: A multinational-multicenter retrospective cohort study. Data was obtained from 18 centers worldwide, anonymously, on wwCF 18-45 years old, including disease severity and outcome, as well as obstetric and newborn complications. Data were analyzed, within each individual patient to compare the outcomes of an initial pregnancy (1st or 2nd) with a multigravid pregnancy (≥3) as well as secondary analysis of grouped data to identify risk factors for disease progression or adverse neonatal outcomes. Three time periods were assessed - before, during, and after pregnancy. RESULTS: The study population included 141 wwCF of whom 41 (29%) had ≥3 pregnancies, "multiparous". Data were collected on 246 pregnancies, between 1973 and 2020, 69 (28%) were multiparous. A greater decline in ppFEV1 was seen in multiparous women, primarily in pancreatic insufficient (PI) wwCF and those with two severe (class I-III) mutations. Multigravid pregnancies were shorter, especially in wwCF over 30 years old, who had high rates of prematurity and newborn complications. There was no effect on pulmonary exacerbations or disease-related complications. CONCLUSIONS: Multiple pregnancies in wwCF are associated with accelerated respiratory deterioration and higher rates of preterm births. Therefore, strict follow-up by a multidisciplinary CF and obstetric team is needed in women who desire to carry multiple pregnancies.
Keywords: těhotenství mnohočetné; stupeň závažnosti nemoci; Pregnancy Complications; Disease Progression; komplikace těhotenství; Retrospective Studies; těhotenství; progrese nemoci; Premature Birth; mladiství; výsledek těhotenství; Middle Aged; Adult; mladý dospělý; Cystic Fibrosis; parita; Infant, Newborn; Young Adult; ženské pohlaví; novorozenec; předčasný porod; retrospektivní studie; Humans; Pregnancy; Pregnancy Outcome; Severity of Illness Index; lidé středního věku; rizikové faktory; dospělí; Female; Risk Factors; Pregnancy, Multiple; Adolescent; Parity; lidé; cystická fibróza